Causal faster-than-light travel from a localized second time coordinate - Nastase, Horatiu [UNESP] (American Physical Society (APS), 2019)
I present a general relativistic model with a compactified second time coordinate that a priori allows for causal, yet faster than light travel in the background of a Friedmann-Lemaître-Robertson-Walker geometry, by local modification of a higher dimensional background geometry, specifically with respect to the radius of the compactified time coordinate. The modification can be induced via the fields of the model. I show that one cannot convert (as possible in special relativistic models, or simple general relativistic models) the superluminality into closed timelike loops violating causality, due to a novel combination of factors, at least for vmax≤2. The physics of the second time is constrained by postulates derived from reasonable physical assumptions. I comment on the possibility of experimental implications of the model.